(untitled) (International Journal of Engineering and Computer Science, 2015)
The analysis of microscopic and macroscopic objects in the real world needs processing of multiple parameter data. The value of each parameter in the three dimensional space varies from point to point. Hence compression of such images poses multiple challenges. In this paper an attempt is made to provide a framework for compressing image data of such objects.